Fermented Deproteinized Alfalfa Juice Modified with Fly Ash Filtrate as an Alternative Nutrient Source for Winter Wheat (Triticum aestivum L.) - Péter Makleit; Andrea Kovács Balláné; Nóra Bákonyi; Éva Domokos-Szabolcsy; Gábor Miklós Fári; Szilvia Veres (Agronomy)
An alternative method of plant nutrition involves the utilization of different by-products. In this study, a combination of two by-products was applied to investigate this method: fermented deproteinized alfalfa juice (FDAJ), a by-product of alfalfa leaf protein production, and fly ash filtrate from a wood-fired power plant. A pot experiment was conducted with winter wheat in an open-sided greenhouse in sandy soil. The aim was to evaluate the efficacy and usability of the combination of these by-products (SFDAJ) for enhanced plant nutrition via spraying or irrigation. Prior to overwintering, photosynthetic pigments, relative chlorophyll content, specific leaf area, and shoot dry weight were measured. At full maturity, we determined morphological parameters, yield, and the element content of the grain. Significant differences were observed between treatments at full maturity. The application of SFDAJ resulted in 73.2% of the yield having the optimal nutrient supply. Compared to the treatment with no nutrients added, the application of SFDAJ increased yields by 260%. Our results show that SFDAJ alone is suitable for providing enhanced nutrient supply in soils with good nutrient supply or in extensive cultivation technology. When supplemented with fertilizer, it can be used on soils with low nutrient supply or in intensive cultivation technology. Based on our results of field applications of SFDAJ, the addition of 10 v v−1% FDAJ via irrigation is recommended.